Perception of parenting practices and parenting styles in research with Iberoamerican adolescents - Gonzales Portillo, Juan (2021)
Systematic research has been conducted as the main target for the present paper regarding the theoretical and methodological perspectives base on the parenting practices and parenting styles in Latin American adolescents. The design chosen was a systematic review, following the PRISMA protocol. The SCOTTISH scale was used to identify the level of scientific evidence of the articles. A total of 72 articles were analyzed. It was found that the most recurrent research constructs are parenting practices and parenting styles, being more widely used the ones related to parenting practices without implying any typification of the role assumed by the parent. Researchers use theories such as Bronfenbrenner's ecological model, Bowlby's attachment theory, and Bandura's social-cognitive theory. Most of the research is oriented from an empirical-analytical research paradigm, with a greater prevalence of non-experimental descriptive and correlational studies. It is concluded that the study of the phenomenon does not lose relevance and depends on the context and population determinants.